2018
DOI: 10.18203/2394-6040.ijcmph20181380
|View full text |Cite
|
Sign up to set email alerts
|

A study on personal protective equipment use among health care providers, Tamil Nadu

Abstract: Background: Personal protective equipment (PPE) limits the health care workers contact with all secretions or biological products. This study was planned to find gaps between use of PPE among the health care providers (HCPs). The objective of the study was to evaluate appropriate use of PPE among health care providers in tertiary centres Tamil Nadu.Methods: A cross sectional study was done during November 2014 to October 2015 in two tertiary health care institutions. All health care providers (Doctors, nurses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 6 publications
0
2
1
Order By: Relevance
“…The present study revealed that a significant number of medical officers did not wear impermeable gowns (p=0.001), gloves (p=0.048), face shields (0.008), goggles (p<0.001) and boots (p<0.001) compared to nurses and minor staff taken together. Contrary to the findings of this study, a study conducted in Tamil Nadu 13 revealed that doctors had significantly good compliance towards using appropriate PPE compared to nurses and technicians (p=0.0001). As highlighted by this study, the shortage of PPE supply was a huge problem in many parts of the world Table 4: Association between job category and wearing PPE Table 5: Reasons given by the participants for not wearing PPE adequately 15,16 and high demand for face masks made the face masks the most scarce PPE 16 as revealed by this study.…”
Section: Discussioncontrasting
confidence: 99%
“…The present study revealed that a significant number of medical officers did not wear impermeable gowns (p=0.001), gloves (p=0.048), face shields (0.008), goggles (p<0.001) and boots (p<0.001) compared to nurses and minor staff taken together. Contrary to the findings of this study, a study conducted in Tamil Nadu 13 revealed that doctors had significantly good compliance towards using appropriate PPE compared to nurses and technicians (p=0.0001). As highlighted by this study, the shortage of PPE supply was a huge problem in many parts of the world Table 4: Association between job category and wearing PPE Table 5: Reasons given by the participants for not wearing PPE adequately 15,16 and high demand for face masks made the face masks the most scarce PPE 16 as revealed by this study.…”
Section: Discussioncontrasting
confidence: 99%
“…This scenario increases considerably the risk of adverse events such as skin reactions. The problem is further complicated by the lack of training and awareness among HCWs about the use of PPE [42,43]. During the COVID-19 pandemic, HCWs have to encounter several challenges regarding PPE such as donning (putting on) and doffing (taking off) equipment in the appropriate way, wearing PPE items for long periods of time, difficulties in communication with patients and colleagues etc.…”
Section: Discussionmentioning
confidence: 99%
“…76 Similar to our study findings, inadequate IPC compliance at 6% during the pre-pandemic period 31 and an 18.1% self-reported compliance level by the health workers have been previously reported. 77 Lower PPE and IPC compliance levels have been attributed to stricter and more objective compliance and adherence observation assessment methods as compared to levels based on subjective and more biased self-reported PPE/IPC compliance assessment methods. We posit that lower overall levels of self-reported adherence to PPE/IPC measures in our study was attrubutable to the study period, 75 whereby, data collection was done when Covid-19 infections rates had waned in the study setting and coincided with progressive easing and relaxation of public health policy mandates on PPE/IPC compliance and other restrictive Covid-19 prevention protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure level (on-adherence to PPE/IPC) of 23.7% among the general population of HWs was selected based on a recent study. 77…”
Section: Recommendationsmentioning
confidence: 99%